Bidirectional positive buck-boost converter - Boora, A.; zare, F.; Ledwich, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2008)
In a positive buck-boost (PBB) converter, inductor current and capacitor voltage can be decoupled which may improve system stability. In fact for a specific level of capacitor voltage, the inductor current can be adjusted at different levels and can be utilized to increase the robustness of the converter against input voltage and load disturbances. But when demand is a fast response with respect to step change in reference voltage, this topology needs to be modified. In this paper, a family of topologies based on a positive buck boost converter are presented which have a fast response and bidirectional power flow capability. This feature leads to some applications in hybrid vehicle systems and telecommunications. Simulations have been carried out to validate fast response of the proposed converters.